Monitored Home-based Exercise Rehabilitation for Patient with Chronic Respiratory and Cardiovascular Diseases During Covid-19 Pandemic: A Case Report - Arnengsih Nazir; Marina Annette Moeliono (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTIntroduction: In patients with Chronic Obstructive Pulmonary Disease (COPD), due to shared-riskfactors, concomitant chronic cardiovascular diseases include Congestive Heart Failure (CHF) arecommon and resulting in increase overall morbidity and mortalit y.Case Report: A female patient, 52 years, came for pulmonary rehabilitation 2 weeks after hospitalizationdue to acute exacerbation of COPD. One week before the exacerbation, she showed symptoms of CHF.Physical examination showed signs of right and left heart failure, oxygen desaturation, and limitedchest expansion. Functional assessment showed disability in self-care, instrumental activities ofdaily living (ADL), deconditioning, depression, and anxiety. Supporting examination confirmed verysevere restriction and obstruction, bronchopneumonia, cardiomegaly, and pulmonary hypertension.Rehabilitation problems include cardiorespiratory, ADL, and psychological problems. The Covid-19pandemic causing prohibition of supervised cardiorespiratory rehabilitation. Home-based exerciseprogram was given for 5 months. Monitoring was done via video call before and after each exercise andthrough analysis of exercise diary. Psychological counseling also given at the beginning of the program.Patient did all of prescribed exercises. At the end, symptoms decreased, patient can do ADL and hobbies,no exacerbation or exercise intolerance, patient does not look anxious and consents to leisure activities.Conclusion: Monitored-home based exercise programs can be used as safely alternative to hospitalbased,if done according to the prescription. However , monitoring by physician is mandatory.Keywords: chronic obstructive pulmonary disease, congestive heart failure, covid-19 pandemic, homebasedexercise, rehabilitation